Peran Kepolisian Dalam Upaya Penegakan Hukum Atas Tindak Pidana Begal Bermotor di Sumatera Utara (Studi Pada Polrestabes Medan) - Andi Putra Silaban; Maswandi Maswandi; Azwir Agus (Jurnal Interpretasi Hukum, 2024)
Indonesia is a country based on law, so every act that violates legal norms in society must be given sanctions according to applicable law. The crime of motorcycle theft committed by muggers is one of the crimes that often occurs in the midst of community life. The role of law enforcement is to make efforts to uphold or function legal norms and provide a sense of security and order in the midst of community life. Based on Article 365 of the Criminal Code, namely a criminal act preceded, accompanied or followed by violence or threats of violence, against people. The obstacles experienced by the Medan Police in revealing the case of the robbery of a motorbike by a mugger are inadequate logistical needs, an indifferent community and the clarity of the victim in providing a report regarding the process of the robbery they experienced. Furthermore, efforts to overcome these obstacles include additional budget funds to overcome the perpetrators of the mugging, socialization to the community regarding the robbery committed by the mugger and taking special steps in handling the mugging case.